2010
DOI: 10.1089/jmf.2009.1207
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Anti-Inflammatory Activity of Bakuchiol fromUlmus davidianavar.japonica

Abstract: The bark of the root and stem of Ulmus davidiana var. japonica has been used as a traditional Korean medicine to treat inflammatory disorders. This plant reportedly exhibits antioxidant, anticancer, and anti-inflammatory effects. A search for biologically active compounds in U. davidiana var. japonica extracts yielded bakuchiol, which we structurally identified on the basis of spectral data, including two-dimensional nuclear magnetic resonance spectroscopy and distortionless enhancement by polarization transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 23 publications
0
37
0
1
Order By: Relevance
“…Regarding the active compounds included in BEE, several candidate compounds such as bakuchiol, mansonone E and F, glycoproteins, and catechins were documented [2,20,27,30]. Those compounds are known to have diverse biological effects including anti-inflammatory, proapoptotic, and anti-oxidative properties according to the isolation method or type of cell line [20,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the active compounds included in BEE, several candidate compounds such as bakuchiol, mansonone E and F, glycoproteins, and catechins were documented [2,20,27,30]. Those compounds are known to have diverse biological effects including anti-inflammatory, proapoptotic, and anti-oxidative properties according to the isolation method or type of cell line [20,30].…”
Section: Discussionmentioning
confidence: 99%
“…Those compounds are known to have diverse biological effects including anti-inflammatory, proapoptotic, and anti-oxidative properties according to the isolation method or type of cell line [20,30]. In particular, bakuchiol and masonone E and F are known to be major components in ethanolic BEE that exert anti-inflammatory or pro-apoptotic effects [2]. Therefore, we assume that these compounds might have been included in the BEE and influenced our results.…”
Section: Discussionmentioning
confidence: 99%
“…(1-(4-hydroxyphenyl)-3,7-dimethyl-3-vinyl-1,6-octadiene, Figure 1), a monoterpene phenol present in seeds and leaves of Psoralea corylifolia (Leguminosae), shows many pharmacological properties such as anti-pyretic (Backhouse et al, 2001), anti-inflammatory (Choi et al, 2010), anti-aging (Chaudhuri & Bojanowski, 2014) and antimicrobial activities (Katsura et al, 2001). More recently, it has been demonstrated that bakuchiol shows considerable anti-tumor effects against human lung adenocarcinoma A549 cells (Chen et al, 2010), SK-MEL-2 human melanoma cells (Madrid et al, 2015) and skin cancer cells (Kim et al, 2016).…”
Section: Bakuchiolmentioning
confidence: 99%
“…Ulmus davidiana var. japonica (UJ) has been planted widely in northern Japan and is used as a traditional medicine for its anti-inflammatory, anti-glycation, and anti-angiogenic activities; further, it exerts protective effects against glutamate-induced neurotoxicity and sepsis (Lee and Kim 2001; Lee et al 2005; Choi et al 2010; Jung et al 2007; Zheng et al 2011). Recently, a new technique has been developed for the production of ultrafine (smaller than 0.1 μm) particles of medicinal herbs.…”
Section: Introductionmentioning
confidence: 99%